Pengaruh Penggunaan Pektin Nabati dengan Persentase yang Berbeda terhadap Nilai pH dan Total Asam Tertitrasi Yogurt Susu Sapi - Naofal Dhia Arkan; Triana Setyawardani; Triana Yuni Astuti (Jurnal Teknologi Hasil Peternakan, 2021)
The research aims to determine the addition of pectin to the production of yoghurt cow’s milk on the pH value and titrated total acid. The material used was 10 liters of cow's milk, 40 grams of pectin, skim milk, yoghurt starter, pH 4 buffer, pH 7 buffer, 1% pp indicator, 0.1 N NaOH solution and distilled water. Experimental research method with Completely Randomized Design (CRD), with 5 treatments, 4 replications, so that there are 20 units. The results of the addition of pectin had no significant effect (P>0,05) on pH value and titrated total acid. The results of the addition of pectin to the manufacture of yogurt have a pH value average of P0 4,69 ± 0,304; P1 4,60 ± 0,354; P2 4,51 ± 0,356; P3 4,41 ± 0,392; P4 4,31 ± 0,431, in the total titrated acid has an average of P0 0,920% ± 0,0867; P1 0,949% ± 0,0948; P2 0,983% ± 0,1132; P3 1,005% ± 0,1176; P4 1,028% ± 0,1178. The addition of pectin up to 0,8% does not chages value of pH and the titrated total acid to yoghurt cow’s milk.